Monitoring Performance in Show Jumping Horses: Validity of Non-specific and Discipline-specific Field Exercise Tests for a Practicable Assessment of Aerobic Performance - Kirsch, Katharina; Fercher, Christina; Horstmann, Stephanie; von Reitzenstein, Caroline; Augustin, Julia; Lagershausen, Henrike (Frontiers in Physiology, 2022)
Show jumping is a highly specialized equestrian discipline that requires technical skill but also power and fitness. Monitoring the horses’ aerobic performance is therefore essential in order to verify whether the training has induced the desired cardiovascular and muscular adaptations. This study therefore aimed at evaluating the validity of non-specific and discipline-specific field exercise tests for objective evaluation of aerobic performance in show jumpers. For this purpose, data obtained from horses competing at Junior and Young Rider level during show jumping competitions as well as field exercise tests were retrospectively analyzed. The effect of the level of difficulty, the horses’ age, the penalty score and the horses’ previous level of performance on blood lactate concentrations after show jumping competitions (49 horses) was evaluated by linear mixed effects models. Estimated marginal means significantly increased from 140 (4.1 mmol/L) to 150 cm (5.2 mmol/L) classes (P = 0.02). Furthermore, post exercise lactate values significantly increased with the horses’ age (P = 0.001). Another group of 12 horses performed a standardized incremental field exercise test on a track (SETtrack), a standardized show jumping course (SETcourse) and a standardized grid exercise (SETgrid) each on 3 consecutive days. Indices of aerobic performance, derived from the SETtrack (velocity at a heart rate of 140 bpm (V140) and at a lactate concentration of 2 mmol/L (VLa2)) were highly correlated with heart rate (V140: r = 0.75, P = 0.005; VLa2: r = 0.66, P = 0.02) and lactate (V140: r = 0.73, P = 0.02; VLa2: r = 0.72, P = 0.02) in response to SETcourse as well as heart rate during SETgrid (V140: r = 0.73, P = 0.02; VLa2: r = 0.76, P = 0.01). Subjective rating of muscular fatigue was significantly correlated to the mean heart rate during SETcourse (r = 0.64, P = 0.05) and SETgrid (r = 0.74, P = 0.02) but not to the aerobic indices calculated from SETtrack. Besides non-specific incremental field tests, performance monitoring in show jumpers should therefore also include discipline specific tests that more closely reflect the internal load induced by show jumping competitions.